Soil-leaf nutrient relationships with fruit quality and yield of litchi (Litchi chinensis) in northern India - SINGH, NAV PREM; SINGH, JAGDISH; SINGH, SARVPRIYA; GILL, PARMPAL SINGH (The Indian Journal of Agricultural Sciences, 2022)
In litchi (Litchi chinensis Sonner.) orchards of northern India, imbalanced nutrient applications and poor soil health status are the major constraints for lower orchard efficiency and poor fruit productivity. Soil and leaf nutrient indexing are considered supportive tools to recognize the nutritional status of litchi orchards and assess the relationship between nutrients, fruit yield and quality attributes. Hence a multi-location study was carried out at Hoshiarpur (S-I), Gurdaspur (S-II), and Pathankot (S-III) districts of Punjab during 2018–20 to study the soil-leaf nutrient relationships with fruit quality and yield of litchi. Nutritional analysis of leaf samples from litchi orchards demonstrated that Ca content was lower in 28.1% of orchards, followed by N (26.4%) and Mn (23.2%). Soil-leaf nutrient matrix was positively and significantly correlated with each other for K, Ca, and Mg content. A significant positive relationship between leaf N and K with fruit yield, size, weight, proportion of pulp (%) and pulp/stone ratio were observed. A significant and negative correlation was registered for colour value (hue angle, hο) with leaf K and Ca contents depicted better pericarp red colour. It was observed that leaf N and K contents are primarily associated with the enhancement of fruit yield. Leaf Ca, Zn, Fe, and Cu content substantially influenced the fruit’s physical and quality parameters of litchi.